2018
DOI: 10.1111/jfbc.12536
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profile by HPLC-MS, biological potential, and nutritional value of a promising food: Monofloral bee pollen

Abstract: The objective of this study was to determine physicochemical and phenolic profiles as well the antioxidant and antimicrobial capacities of monofloral bee pollen samples from Brazil. Traditional methods were used. The phenolic profile was determined by high‐performance liquid chromatography‐mass spectrometry (HPLC‐MS). The protein (10.6–33.9 g/100g), lipids (3.2–8.3 g/100g), ashes (2.6–3.8 g/100g), total phenolic (5.6–29.7 mg GAE/g), and total flavonoid (0.3–19.0 mg QE/g) values were variable, even between prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 38 publications
10
29
0
Order By: Relevance
“…Some researchers have already suggested that bee pollen composition can vary depending on its geographical and botanical origins (Bogdanov, 2012;Campos et al, 2008;Carpes et al, 2008;De-Melo et al, 2018;Yang et al, 2013); which could explain the difference in composition of the samples analysed in the present study. According to De-Melo and Almeida-Murdian (2017), climatic conditions, soil characteristics as well as age and nutritional state of the plant influence the development and composition of the pollen grains and, consequently, the bee pollen composition produced from these grains.…”
Section: Physicochemical Parameters and Biological Potentialmentioning
confidence: 74%
See 4 more Smart Citations
“…Some researchers have already suggested that bee pollen composition can vary depending on its geographical and botanical origins (Bogdanov, 2012;Campos et al, 2008;Carpes et al, 2008;De-Melo et al, 2018;Yang et al, 2013); which could explain the difference in composition of the samples analysed in the present study. According to De-Melo and Almeida-Murdian (2017), climatic conditions, soil characteristics as well as age and nutritional state of the plant influence the development and composition of the pollen grains and, consequently, the bee pollen composition produced from these grains.…”
Section: Physicochemical Parameters and Biological Potentialmentioning
confidence: 74%
“…when analysing Zea mays monofloral bee pollen from Portugal, Brazil and Mexico, observed that the profiles did not vary during the sampling period (2000-2012) or according to geographic origin. The same did not occur with Mimosa scabrella monofloral bee pollen analysed by De-Melo et al (2018), since the authors observed different phenolic profiles according to the Brazilian region from which the samples were collected. They attributed the variation to agronomic or genotypic differences between the plants as well as climatic and soil conditions that could influence the pollen composition of Mimosa scabrella.…”
Section: Tablementioning
confidence: 82%
See 3 more Smart Citations